A procedure for validating fixed-base driving simulators - Losa, Massimo; Frendo, Francesco; Cofrancesco, Armando; Bartolozzi, Riccardo (Transport, 2013)
This paper aims to define a standard procedure for validating a fixed-base driving simulator to be used for road safety studies and in the automotive field for development of new vehicle-subsystems. The driving simulator was developed at the University of Pisa (Italy) – Department of Mechanical, Nuclear and Production Engineering; it is characterized by a static cockpit and a single front projection channel, with vehicle and pedestrian traffic opportunely generated. The validation procedure consisted in a statistical comparison between data recorded by an instrumented vehicle on an urban path and those recorded by the driving simulator on the same path reproduced in virtual reality. A sample of 93 volunteers were submitted to both the drive tests during which several vehicle signals, such as speed data, acceleration, braking action, engine RPM and steering angle were continuously stored. Speed and acceleration data were subsequently analysed through conventional statistical methods (z-test); in order to evaluate differences between real and simulated driving, the statistical analysis was integrated by regression techniques. The analysis allowed to highlight the efficiency of the procedure in both the relative and absolute validation process as well as to evaluate potentials of the specific driving simulator. The procedure has general validity and can be used as a standard procedure for validation of fixed-base driving simulators. First Published Online: 24 Dec 2013